Potensi Fungsi RAP (Reclaimed Asphalt Pavement) sebagai Bahan Lapis Pondasi (Base) - Noviarti, Triafini; Putra, Sasana; Herianto, Dwi (Universitas Lampung, 2019)
Material requirements for road pavement have increased along with major developments in Lampung Province. This causes the availability of aggregates to become thinner. One alternative replacement material is RAP (Reclaimed Asphalt Pavement). The aggregate in RAP becomes a potential that can be used as a basic material for road foundation layer. Therefore, research on the potential of RAP (Reclaimed Asphalt Pavement) if used as a base course material.This study uses RAP material obtained from the asphalt pavement layers on Soekarno-Hatta Street, Bandar Lampung. The results of the maximum dry density value obtained from three behaviors amount of blow is 1.965 grams / cm3, so that the resulting CBR value is 51%. This is caused during mixing and blows, the added water cannot enter perfectly into the RAP cavity. Because RAP granules are coated with asphalt so it is impermeable. So it can be concluded that the potential RAP used in this study cannot be used in road foundation layer class A but can be used as a road fondation layer class S. And if an additional of blows are made in each layer, RAP potentially can be used as a class B road foundation material. Keywords : RAP (Reclaimed Asphalt Pavement), Base Course, Optimum Moisture Content.